2020
DOI: 10.3389/fmicb.2020.01810
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Microbiomes of Suppressive Composts for Plant Protection: From Metagenomes to Beneficial Microorganisms and Reliable Diagnostics

Abstract: Harnessing Microbiomes of Suppressive Composts of action of biocontrol strains. Integrating the benefits of these approaches will bring the long-term goals of employing microorganisms for a sustainable control of plant pathogens and developing reliable diagnostic assays to assess the suppressiveness of composts within reach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 120 publications
1
32
2
Order By: Relevance
“…Moreover, compost batch was shown to be the most important to determine bacterial and fungal community composition. Lutz et al (2020) also state that microbial community composition is highly dependent on the initial characteristics of the composts, including the compost material. A previous study by Vandecasteele et al (2021) showed that optimizing chemical properties of composts for a better fit in growing media was only successful if composts initially had a good suitability score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, compost batch was shown to be the most important to determine bacterial and fungal community composition. Lutz et al (2020) also state that microbial community composition is highly dependent on the initial characteristics of the composts, including the compost material. A previous study by Vandecasteele et al (2021) showed that optimizing chemical properties of composts for a better fit in growing media was only successful if composts initially had a good suitability score.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, composts are characterized by high microbial activity that may stimulate plant growth and disease suppression ( Hoitink et al, 1996 ; Noble and Coventry, 2005 ; Raviv, 2008 ). Diverse potential biocontrol agents present in composts, such as Trichoderma , Pseudomonas , Pantoea and Bacillus spp., are known to contribute to a biocontrol effect ( Dukare et al, 2011 ; Chen et al, 2012 ; Antoniou et al, 2017 ; Lutz et al, 2020 ). This is in contrast to peat, which is considered to be poor in microorganisms, either beneficial or neutral, as compared to alternative growing media containing composts or other renewable materials, due to the recalcitrant chemical composition of Sphagnum biomass ( Hoitink and Boehm, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compost represents an important source of organic matter and nutrients for agriculture, playing a crucial role in sustaining soil biodiversity [ 16 ] and the production of horticultural species when used as a component in the preparation of pot substrates [ 17 ]. Moreover, the microflora of the compost have significant antagonistic effects against several soil-borne phytopathogenic microorganisms, and hence they can play a vital role in controlling them [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in high-throughput sequencing have revolutionized genomic discovery and unlocked new insights regarding the diversity and function of microbial communities (1)(2)(3)(4). For example, shotgun metagenomic sequencing has clarified how the functional capacity of the gut microbiome links to human health (5)(6)(7)(8), improved the efficacy of antibiotic resistance gene discovery (9)(10)(11)(12), identified beneficial soil microbes for agricultural use (13)(14)(15), and uncovered novel, medically relevant biosynthetic gene clusters in marine microbes (16)(17)(18). However, while metagenomes offer rich opportunity to transform discovery, the financial cost of producing metagenomic data limits their application.…”
Section: Introductionmentioning
confidence: 99%